Socioeconomic Inequalities in Different Types of Disabilities in Iran - Ghobad MORADI; Farideh MOSTAFAVI; Mohammad HAJIZADEH; Mohammad AMERZADE; Amjad MOHAMMADI BOLBANABAD; Cyrus ALINIA; Bakhtiar PIROOZI (Tehran University of Medical Sciences, 2018)
Background: This study measured socioeconomic inequalities in different types of disabilities in Iran. We also examined the prevalence of disabilities across different socio-demographic groups in Iran in 201 Methods: This was cross-sectional study using secondary data analysis on all Iranian. Data related to disability prevalence and socioeconomic status (SES) of each province was extracted from the 2011 National Census of Population and Housing (NCPH) and the 2011 Households Income and Expenditure Survey (HIES), conducted by Statistical Center of Iran (SCI). The concentration index and concentration curve were used to measure and illustrate socioeconomic inequalities in different types of disabilities. Chi-squared test was also used to examine the relationship between the socio-demographic variables (age-groups, sex, education level, employment status) and disability. Results: The results suggested the existence of socioeconomic inequalities in blindness, deafness, vocal disorders and hand disorders in Iran. The concentration index for these four disabilities were -0.0527 (95% confidence interval [CI]: -0.0881, -0.0173), -0.0451 (CI: -0.0747, -0.0156), -0.0663 (CI: -0.1043, -0.0282) and -0.0545 (CI: -0.0940, -0.0151), respectively. There were also significant associations between the demographic variables such as age-groups, sex, education level, employment status and disability (P<0.05). Conclusion: There were significant socioeconomic inequalities in different types of disabilities in Iran with poorer provinces having higher prevalence of disabilities in blindness, deafness, vocal disorders and hand disorders. Strategies to address the higher prevalence of different types of disabilities among poorer provinces should be considered a priority in Iran.